Alih Wahana Game Touken Ranbu Menjadi Drama Musikal sebagai Representasi Identitas Latar dan Budaya Jepang - Sri Wahyuningtyas; Widowati Widowati; Herning Puspitarini (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2018)
This paper adopts the phenomenon of electronic literature or hybrid literature in the form of online game namely Touken Ranbu which is converted to a musical drama entitled Touken Ranbu Bakumatsu Tenrouden. The object is examined by using transformation studies which is related to the technology utilization as a means to elevate culture and history to be recognized by society. The problem identification in this paper is analyzing the similarity and difference in the game and musical drama of Touken Ranbu as well as the setting and cultural elements contained in it.The result of this paper is that there are similarity in the theme and differences in additional of characters, plot, and setting. Moreover, the cultural setting and Japan cultural elements which are highlighted in the object are in the form of sword symbol and samurai figure as a symbol of the struggle and life view of the society. Therefore, through a literary work in the form of Touken Ranbu game dan the musical drama, culture and history could be a learning which is bequeathed to the young generation.